Assessment of Land use and Land Cover Change in Kwale, Ndokwa-East Local Government Area, Delta State, Nigeria (Global Journal of Human-Social Science, 2014)
Abstract not found
Keywords: land use; change; remote sensing; GIS; kwale; nigeria